Accelerating aroma formation of raw soy sauce using low intensity sonication. (1st November 2020) - Gao, Xianli; Liu, Ermeng; Zhang, Junke; Yang, Lixin; Huang, Qingrong; Chen, Sui; Ma, Haile; Ho, Chi-Tang; Liao, Lan
Highlights: Sonication accelerated aroma formation of soy sauce and reduced fermentation time by 90 days. Sonication facilitated soy sauce aroma formation by lowering activation energy of reaction. Sonication enhanced microbial growth, which increased the rate of aroma formation. Abstract: Sonication was applied to accelerate aroma formation and shorten fermentation time of soy sauce. Effects of sonication at 68 kHz on the aroma and aroma-producing Zygosaccharomyces rouxii and Tetragenococcus halophilus in moromis were investigated using sensory evaluation, SPME–GC–olfactometry/MS, viable cell counting and scanning electron microscopy. The sensory scores of caramel-like, fruity, alcoholic, floral, malty, smoky, sour and overall aroma in sonicated moromis were enhanced by 23.4%, 23.2%, 13.6%, 12.8%, 7.6%, 6.3%, 5.6% and 14.4%, respectively. Sensory scores of samples fermented for 90–180 days were higher than those of controls fermented for 180 days, suggesting that sonication could reduce fermentation time by 90 days. Thirty-four aroma-active compounds were detected from 85 volatile compounds in soy sauces. Sonication accelerated and elevated the formation of aroma compounds by chemical reactions. It also markedly increased the reproduction and cell permeability of both microorganisms in moromis, which favored the formation of aroma compounds by both strains.